PIV validation of different turbulence models used for numerical simulation of a centrifugal pump diffuser. Issue 1 (5th March 2018) - Zhou, Ling; Bai, Ling; Li, Wei; Shi, Weidong; Wang, Chuan
Abstract : Purpose: The purpose of this study is to validate the different turbulence models using in the numerical simulation of centrifugal pump diffuser. Computational fluid dynamics (CFD) has become the main method to study the pump inner flow patterns. It is important to understand the differences and features of the different turbulence models used in turbomachinery. Design/methodology/approach: The velocity flow fields in a compact return diffuser under different flow conditions are studied and compared between CFD and particle image velocimetry (PIV) measurements. Three turbulence models are used to solve the steady flow field using high-quality fine structured grids, including shear stress transport (SST) k-w model, detached-eddy simulation (DES) model and SST k-w model with low-Re corrections. Findings: SST k-w model with low-Re correction gives better results compared to DES and SST k-w model, and gives a good predication about the vortex core position under strong part-loading conditions. Originality/value: A special test rig is designed to carry out the 2D PIV measurements under high rotating speed of 2850 r/min, and the PIV results are used to validate the CFD results.